The effect of high-intensity functional training on performance and oxidative stress in adolescent soccer players (Development Engineering Conferences Center Articles Database, 2025)
While regular exercise training is known to decrease oxidative stress (OS) and enhance antioxidant functions in adults, limited data exist on OS responses in the pediatric population. This study aimed to investigate the effects of high-intensity functional training (HIFT) on oxidative stress and physical performance in adolescent soccer players. In this randomized controlled trial, 20 well-trained adolescent soccer players were divided into HIFT (n=10) and moderate-intensity soccer technical training (MITT, n=10) groups. Both groups trained for 8 weeks (3 days/week). Oxidative stress biomarkers (MDA, 8-OHDG, H2O2, GPx, CAT) and physical performance (VO2peak, vertical jump height [VJH], maximal explosive power [MEP]) were assessed pre- and post-intervention. Repeated measure mixed ANOVA (2×2) with a significance level of P